Executive function and suicidality: A systematic qualitative review. (August 2015) - Bredemeier, Keith; Miller, Ivan W.
Abstract: Deficits in executive function (EF) have been proposed as a possible explanation for the "cognitive rigidity" often observed in suicidal individuals. This article provides a systematic review of the existing literature testing the relations between EF and suicidality, across various diagnostic and demographic populations, using the influential multidimensional model of EF proposed by Miyake and colleagues (2000) as an organizing framework. Forty-three journal articles on this topic published before January of 2014 were reviewed. Collectively, results from these studies provide tentative support for an association between EF deficits and suicidality. However, there is some evidence that this association is moderated by other factors (e.g., suicide attempt lethality). Importantly, this relationship may vary across diagnostic groups. Specifically, more studies that used depressive disorder samples reported some positive findings (75%), followed by mixed diagnostic samples (54%). In contrast, fewer positive findings have emerged from studies with bipolar or psychotic disorder samples (29% and 33% respectively), and some even found that suicidality is associated with better EF in individuals with psychotic disorders. Firm conclusions about relationships between specific dimensions of EF and/or aspects of suicidality are difficult to draw this time. Limitations of the existing literature and corresponding directions for future research are discussed. Highlights: We reviewed the literature on links between executive function (EF) and suicidality. 43 articles examining this issue in different diagnostic populations were located. There is tentative support for an association between EF deficits and suicidality. However, this relationship may vary across diagnostic populations. Limitations of this research and recommendations for future work are discussed.